Energy metabolism disorders in migraine: triggers, pathways, and therapeutic repurposing - Sun, Wen-xiu; Chen, Ting-yan; Song, Mao-mei; Gao, Ying-jie; Xu, Sui-yi (Frontiers in Neurology, 2025)
Many migraine triggers, such as stress, sleep deprivation, fatigue, strenuous exercise, and fasting, are potentially linked to disturbances in brain energy metabolism, mitochondrial function, and oxidative stress. Alongside efforts to avoid modifiable factors, prophylactic migraine treatments that target brain energy metabolism have garnered increasing attention. However, the current evidence supporting the use of energy-modulating drugs in migraine treatment guidelines remains weak. This narrative review explores the relationship between energy metabolism and cortical spreading depression susceptibility, metabolic alterations in migraine (including glucose and insulin metabolism, insulin resistance, lipid metabolism, and energy metabolism imaging markers), oxidative stress and antioxidant defenses, mitochondrial dysfunction, and the role of energy metabolism-targeted medications in migraine management. Nutrients may help improve mitochondrial function, thereby alleviating brain energy metabolism deficits and oxidative stress in migraine.